Enhancement of Cross-Borehole Pulse Radar Signature on a Partially Water-Filled Tunnel. (16th December 2014) - Jung, Ji-Hyun; Kim, Se-Yun
Abstract : Cross-borehole pulse radar has been employed to detect a deeply located empty tunnel. In this paper, effects of underground water collected in the bottom of an empty tunnel on cross-borehole pulse radar signatures are analyzed numerically. B-scan images, stacks of received pulses, are calculated by applying the finite-difference time-domain (FDTD) method for 6 different heights of water from the bottom to the half height inside an empty tunnel. The most important features of an empty tunnel, the fastest time of peak (TOP) and time of arrival (TOA) extracted from the B-scan images, are slowed considerably depending on the increased height of water inside the tunnel. To compensate the weak TOP like that of an empty tunnel, a relation curve is formulated only utilizing measurable parameters of the fastest TOP and the fastest TOA. Then, a unified curve including the effects of two granites with the low and high dielectric properties is derived to cover widely varied dielectric properties of underground rocks. Based on the fastest TOP of an empty tunnel, the average difference between the fastest TOP of an empty tunnel and that of a partially water-filled tunnel decreases from 22.92% to 2.59% after enhancement.